Study of thermal resistance and regulation mechanisms in nickel slag-slag based binary geopolymers - Jize Wang; Sixiang Kang; Dongliang Zhang; Wenda Wu; Feng Zhang; Xuefang Wang; Liwei Xu; Jipeng Zhang (Case Studies in Construction Materials)
To efficiently and environmentally utilize industrial waste nickel slag and enhance the high-temperature performance of construction materials, this study prepared a binary geopolymer using nickel slag and blast furnace slag as raw materials. By leveraging the advantages of both materials and adjusting the ratio between nickel slag and blast furnace slag, the thermal stability of the geopolymer at high temperatures was improved. This study examined the mechanical properties, mass loss, and thermal deformation behavior of the geopolymer under high-temperature exposure. X-ray diffraction (XRD) and thermogravimetric analysis (TGA) were employed to examine the decomposition and phase transformation of the geopolymer at elevated temperatures. Mercury intrusion porosimetry (MIP) and scanning electron microscopy (SEM) were used to characterize the pore structure and microstructure after exposure to various high temperatures. The results revealed that the formation of novel phases, including diopside, forsterite, and spinel, significantly enhances the thermal stability of the geopolymer incorporating nickel slag. Additionally, the C-(A)-S-H gel formed during slag hydration fills the pores, improving the matrix density. This contributes positively to the high-temperature resistance of geopolymers with high slag content. Overall, with a blending ratio of 20 % nickel slag and 80 % blast furnace slag, the geopolymer achieved a compressive strength of 59.7 MPa at 28 days. Under high-temperature conditions of 200, 400, 600, and 800°C, the compressive strength retention of the geopolymer increased by 11.5 %, 24.8 %, 10.8 %, and 5.8 %, respectively, compared to the pure blast furnace slag system. Additionally, mass loss was reduced by 1.01 %, 0.81 %, 0.73 %, and 0.7 %, and thermal shrinkage at 800°C was reduced by 3.07 %. Given its superior high-temperature resistance, the nickel slag-slag based binary geopolymers holds promise as a new type of green building material suitable for high-temperature environments.